Pengaruh Komitmen Organisasi terhadap Organizational Citizenship Behavior pada Pegawai Instansi X Kota Banjarbaru - Sylva Anggelina As. Nyagin; Julaibib .; Lita Ariani (CV. ITTC INDONESIA, 2025)
Organizational Citizenship Behavior (OCB) refers to employees' voluntary behaviors that extend beyond their formal duties but contribute to the organization's success. These behaviors are influenced by a sense of belonging and include actions such as helping colleagues, adhering to rules, and participating in organizational activities. This study aimed to examine whether organizational commitment influenced OCB. The research employed a correlational quantitative design with a purposive sampling technique. The population consisted of 67 employees from Institution X, with a sample of 51 non-structural employees. Data collection was conducted through Google Forms and direct questionnaire distribution, using an OCB scale and an organizational commitment scale. The data were processed using simple linear regression analysis in JASP 0.19.3. Assumption tests, including normality and linearity tests, were performed. The analysis revealed a significant positive influence, indicating that higher organizational commitment significantly contributed to higher OCB. The findings suggested that enhancing OCB could be achieved by strengthening organizational commitment through improved internal communication, instilling organizational values, and providing employee recognition.